IPTEKS STANDAR PELAYANAN MINIMAL PADA DINAS PEKERJAAN UMUM DAN PENATAAN RUANG DAERAHPROVINSI SULAWESI UTARA. - Londo, Ireine P.; Suwetja, I Gede (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
Reform in administration of government in Indonesia have cause the occurance of a number important and fundamental changes in governance which ultimately has implication for the implementation of public services in the region. In accordance with the provisions of article 11 and article 14 ofLaw of Year 2004 Number 32 concerning Regional Government, Government Regulation Number 65 of 2005 concerning Guidelines for Preparation and Application of Minumum Standards Service (SPM). The Government Regulation is a reference for the Ministry / Institutions in the preparation of MSS and become reference points for the government regions in implementing SPM (MSS).Basic services in the Minimum Service Standards are compulsory government affairs that are carried out by regional Governments both Provincial and Regional Governments. Government Affairs is obligatory relating to basic services which subsequently becomes the type of SPM, one of which is SPM in the Field Public Works. Types of Basic Services for SPM in Public Works and Spatial Planning for Provincial and District / City Governments are as follows. Provincial government : meeting the needs of bulk drinking water across districts / cities and provision of cross-regency / municipal regional domestic wastewater treatment service Keywords : Minimum Service Standards, Implementation, Government